2021
DOI: 10.3390/ijms22189993
|View full text |Cite
|
Sign up to set email alerts
|

An Inducible and Vascular Smooth Muscle Cell-Specific Pink1 Knockout Induces Mitochondrial Energetic Dysfunction during Atherogenesis

Abstract: DNA damage and mitochondrial dysfunction are defining characteristics of aged vascular smooth muscle cells (VSMCs) found in atherosclerosis. Pink1 kinase regulates mitochondrial homeostasis and recycles dysfunctional organelles critical for maintaining energetic homeostasis. Here, we generated a new vascular-specific Pink1 knockout and assessed its effect on VSMC-dependent atherogenesis in vivo and VSMC energetic metabolism in vitro. A smooth muscle cell-specific and MHC-Cre-inducible flox’d Pink1f/f kinase kn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 20 publications
(42 reference statements)
0
8
0
Order By: Relevance
“…XF24 quantifies oxidative phosphorylation by measuring oxygen consumption rate (OCR) as a direct measure of complex 4 activity as the terminal electron acceptor of the mitochondrial respiratory chain, while simultaneously measuring extracellular acidification rate (ECAR) as cytoplasmic milli-pH as in index of glycolysis through glucose to lactate conversion. Drug doses for energetic assays were all 1 µM final concentration for mitochondrial inhibitors oligomycin, FCCP and rotenone, and myxothiazol, and 2-deoxy-glucose (25 mM) to competitively inhibit glucose (2.5 mM), as previously published [ 15 ]. In vivo, soluble Klotho is found to have a wide range of physiological doses (pg–ng) [ 16 ].…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…XF24 quantifies oxidative phosphorylation by measuring oxygen consumption rate (OCR) as a direct measure of complex 4 activity as the terminal electron acceptor of the mitochondrial respiratory chain, while simultaneously measuring extracellular acidification rate (ECAR) as cytoplasmic milli-pH as in index of glycolysis through glucose to lactate conversion. Drug doses for energetic assays were all 1 µM final concentration for mitochondrial inhibitors oligomycin, FCCP and rotenone, and myxothiazol, and 2-deoxy-glucose (25 mM) to competitively inhibit glucose (2.5 mM), as previously published [ 15 ]. In vivo, soluble Klotho is found to have a wide range of physiological doses (pg–ng) [ 16 ].…”
Section: Resultsmentioning
confidence: 99%
“…Previously, we identified loss of mitochondrial homeostasis as key to this phenotype in human atherosclerosis [ 1 ]. More recently, we showed that a switch to glycolytic metabolism as a potential survival mechanism could delay these effects [ 15 ]. Here, we undertook a novel drug screen that investigated the role of compounds previously identified as having an energetic switching role through AMPK and are predicted to positively impact energy balance.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Pink1 kinase regulates mitochondrial homeostasis and recycles dysfunctional organelles critical for maintaining energetic homeostasis. In their study, Docherty et al generated a new vascular-specific Pink1 knockout and assessed its effect on VSMC-dependent atherogenesis in vivo and VSMC energetic metabolism in vitro [ 16 ]. During atherogenesis, the authors found that Pink1 knockout affects the development of plaque quality rather than plaque quantity by decreasing VSMC and extracellular matrix components, collagen and elastin [ 16 ].…”
mentioning
confidence: 99%